(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
We have revealed more than 200 accumulations of slag, foundries and the ancient exploitation excavations. Our investigations and the analysis of literature data bring us to some conclusions. Discovery of slags, ore debris and root way outs of magnetite sandstones like Haghartsin deposit of iron in the basins of the rivers Martziget (Alaverdi Region), Getik (Idjevan Region), the slope of the mountain Maylekh, on the Semyonov crossing, broadens the perspectives of revealing new big deposits of magnetite sandstones. As the requirements were on a small scale, the quantity of stocks, for the metallurgy of the ancient world, did not play an important role. The necessary conditions were deposition of ore bodies near surface, rich content of the metal, location of the deposit in the places approachable for a man, enough quantity of wood. The distance of slag accumulations from exploitations doesn’t exceed 1-2 km, hence there is an opportunity to use slag as exploring sign. We are sure that there is a connection between "Lightning-Sword" from Armenian epos "David of Sasun" and the secret of getting iron by the direct renewal from magnetite ore.